If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(6p + 7) = 87 Reorder the terms: -3(7 + 6p) = 87 (7 * -3 + 6p * -3) = 87 (-21 + -18p) = 87 Solving -21 + -18p = 87 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + -18p = 87 + 21 Combine like terms: -21 + 21 = 0 0 + -18p = 87 + 21 -18p = 87 + 21 Combine like terms: 87 + 21 = 108 -18p = 108 Divide each side by '-18'. p = -6 Simplifying p = -6
| y-160=40[x-1] | | g(x)=-4f(x)+7 | | -7x=-39 | | -0.3-7.6p=-26.14 | | n+5=72 | | 12z-4=4z | | z=5xy-3 | | g(x)=4f(x)-1 | | 2=15*x | | 12a+3+2a-1= | | 750-50x=-185-35x | | 2-(2*y)=y+64 | | 7x^2-4+x=15x | | 2=110*x | | y-5=y-9 | | 6x^2-4x+0=0 | | 53-x+8=4x-27+1 | | (2w+3)2+2x=42 | | 3(7-2k)=57 | | -8+4m^2-5m^2= | | 7x+3-2x+9=47 | | z-8.4=4 | | (x+(2+i))(x+(2-i))=0 | | -0.2(212-h)=8.6 | | 5x-10=39 | | 5.25b=22.75 | | -5x-2=-x-7 | | 3(x+1)+3(x+3)= | | 14x-(4x-5)=45 | | 7x-26=2x+54 | | -7(5k-5)=-210 | | 25-3u=24 |